Learning Journal and the Students’ Achievement in Grammar Class: Transitivity Analysis - Isti'anah, Arina (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
Learning journal enables students to reflect of what they have experienced in the learning process. This article presents the students’ learning journal in grammar class. For some students, grammar is seen as a course which does not attract their interest. It resulted on their ignorance of the course. However, students have to face the fact that grammar is an integral part of their literacy as it affects the meaning of their utterances, both spoken and written. The participants involved were the 37 students of English Letters Department, Sanata Dharma University. The students were in Structure IV course, one of grammar classes offered by the study program. The instruments involved were the students’ learning journal wrtten during the semester and their final grades. The learning journal was analyzed by means of Halliday’s transitivity. The findings reveal that most of the students used material process in their learning journal, while mental and relational processes do not appear often in the journal. The students’ achievement in class is dominated by an A in the end of the semester. Relating the two findings above, this article concludes that students’ practice of their knowledge in their social life affects their achievement in class. The employment of material process in the students’ learning journal reveals the students’ practice and purpose of learning grammar. Keywords: learning journal, grammar, transitivity